The Mythologization of the Abrek's Image in the Modern Caucasian Linguistic Consciousness - Irina S. KARABULATOVA; Svetlana A. LYAUSHEVA; Zaineta R. KHACHMAFOVA; Irina P. SAVCHUK; Oksana S. SHIBKOVA (Astra Salvensis, 2019)
The modern realities of our world actualize the phenomenon of the militant, accentuating the primary fears of the recipient before uncontrolled power, lack of spirituality, darkness, etc. The bearers of European culture are defenseless against the archetypal Evil. We are considering the phenomenon of abrek, which correlates with the image of the militant. If the image of abrek has a positive color in the traditional Caucasian worldview, then modern Russian speakers paint it in a negative aspect. The Abrek phenomenon as a representative of some dark forces was not the object of close attention of the scientific community and for various reasons has not received a clear interpretation and / or understanding. At the same time, the abrek-militant appears in the Caucasian worldview as a bearer of Light and Good. This distinction in the interpretation of the image of abrek is due to the dichotomy of "one's own" in Russian and Caucasian cultures. The formation of a rigid connection between Muslim culture, terrorism and extremism and the Caucasian phenomenon of “abrechestvo”/ abrekticism puts us in a position to investigate the dynamics of the emotional and evaluation characteristics of the abrek lexeme in the contemporary linguistic consciousness of Chechens. The choice of this ethnic group is due to the fact that: 1) this people retained the tradition of “abrechestvo” \ abrekticism; 2) the representatives of this people actively participate in military operations in Syria; 3) the culture of the Chechens is mythologized in the minds of the peoples-neighbors. Today, under the influence of the media, we develop speech markers of portraits of individual ethnic and social groups, which subsequently govern our social behavior.